2018
DOI: 10.2147/copd.s173472
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of inhaled medications (ICS/LABA, LAMA, LAMA/LABA and SAMA) for COPD: a systematic review and network meta-analysis

Abstract: PurposeTo assess the comparative efficacy of short-acting muscarinic antagonists (SAMAs), long-acting muscarinic antagonists (LAMAs), LAMA in combination with long-acting beta-agonists (LABAs; LAMA/LABAs) and inhaled corticosteroids (ICS) in combination with LABA (ICS/LABAs) for the maintenance treatment of COPD.Materials and methodsWe systematically reviewed 74 randomized controlled trials (74,832 participants) published up to 15 November 2017, which compared any of the interventions (SAMA [ipratropium], LAMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 91 publications
1
15
0
Order By: Relevance
“…A recent meta-analysis and systematic review found that the use of fixed-dose LAMA/LABA inhalers resulted in the greatest FEV 1 improvement at weeks 12 and 24 in COPD patients compared to the use of a short-acting MRA (SAMA) alone, LAMA alone or fixed-dose ICS/LABA 59. Similarly, the current review of the efficacy of inhaled UMEC/VI confirms its effectiveness and safety in COPD patients.…”
Section: Fixed-dose Combination Inhaler Of Umec/vi/fluticasone Furoatesupporting
confidence: 62%
“…A recent meta-analysis and systematic review found that the use of fixed-dose LAMA/LABA inhalers resulted in the greatest FEV 1 improvement at weeks 12 and 24 in COPD patients compared to the use of a short-acting MRA (SAMA) alone, LAMA alone or fixed-dose ICS/LABA 59. Similarly, the current review of the efficacy of inhaled UMEC/VI confirms its effectiveness and safety in COPD patients.…”
Section: Fixed-dose Combination Inhaler Of Umec/vi/fluticasone Furoatesupporting
confidence: 62%
“…Although previous pairwise meta-analyses found that ICS/LAMA/LABA had benefits in reducing lung function decline and preventing acute exacerbations compared with LAMA/LABA [27] and ICS/LABA [28], mortality was not evaluated. The significant benefit of reducing all-cause mortality in the inhaled drug classes was not elucidated in recent NMAs [5][6][7]. Our study including all available 219 RCTs found that ICS/LAMA/LABA reduced all-cause mortality compared with the other inhaled therapies, except for ICS/LABA.…”
Section: Discussionmentioning
confidence: 62%
“…A recent pairwise meta-analysis showed that ICS/ LAMA/LABA was associated with a lower risk of exacerbations but failed to reveal the efficacy in reducing mortality in any drug class [4]. Two additional network meta-analyses (NMAs) have been performed, but these studies included neither recent important large randomized controlled trials (RCTs) [5] nor RCTs investigating ICS/LAMA/LABA [6,7]. Safety issues, including pneumonia with ICS [8][9][10] and cardiovascular events with LAMA and LABA [11,12], also cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…8 Additionally, a number of systematic reviews and meta-analyses pertaining to inhaled therapies for COPD have been published recently; however, these did not review observational research. [9][10][11] In this systematic review and network meta-analysis (NMA), we investigate which inhaled therapy strategy is most effective at reducing exacerbation risk, improving lung function, improving health-related quality of life and minimising adverse events in patients with COPD. Here we examine the risk benefit of inhaled therapies, with particular emphasis on triple therapy (LAMA+LABA+ICS) versus LAMA+LABA.…”
Section: Open Accessmentioning
confidence: 99%